Utilize oxygen boosting aeration technical process high concentration organic waste water's equipment - LIN WEI; LIU RENYUAN; GU YONGKUN; LUO LILI; CHEN CHUAN (2016)
The utility model discloses an utilize oxygen boosting aeration technical process high concentration organic waste water's equipment, belong to high concentration organic wastewater equipment technical field, its technical essential includes that the wastewater collection pond reaches and the clean water basin and the SBR reactor of wastewater collection pond difference tube coupling, wherein the bottom is equipped with the micropore aeration device in the wastewater collection pond, and this micropore aeration device has a gas holder through oxygen -rich gas output tube connected, the gas holder is connected with the gas mixing ware through the oxygen -rich gas input tube, the gas mixing ware is connected with the pure oxygen jar through the oxygen input tube, is connected with the air compressor machine through air inlet duct, the utility model aims at providing a compact structure, convenient to use and respond well utilize oxygen boosting aeration technical process high concentration organic waste water's